The effect of out-of-focus blur on visual discomfort when using stereo displays - Blum, T; Wieczorek, M; Aichert, A; Tibrewal, R; Navab, N (2010 9th IEEE International Symposium on Mixed and Augmented Reality, 2010)
Visual discomfort is a major problem for head-mounted displays and other stereo displays. One effect that is known to reduce visual comfort is double vision, which can occur due to high disparities. Previous studies suggest that adding artificial out-of-focus blur increases the fusional limits, where the left and right image can be fused without double vision. We investigate the effect of adding artificial out-of-focus blur on visual discomfort using two different setups. One uses a stereo monitor and an eye tracker to change the depth of focus based on the gaze of the user. The other one uses a video-see through head mounted display. A study involving 18 subjects showed that the viewing comfort when using blur is significantly higher in both setups for virtual scenes. However we can not confirm without doubt that the higher viewing comfort is only related to an increase of the fusional limits, as many subjects reported that double vision did not occur during the experiment. Results for additional photographed images that have been shown to the subjects were less significant. A first prototype of an AR system extracting a depth map from stereo images and adding artificial out-of-focus blur is presented.